Peran Humas Digital dalam Publikasi Konten Pencegahan Narkoba melalui Media Sosial Badan Narkotika Nasional Republik Indonesia - Ivani Valerine Silalahi; Guruh Ramdani; Harries Marithasari (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
This study analyzes the role of BNN RI Public Relations in utilizing social media such as Instagram, TikTok, and YouTube to disseminate information on preventing drug abuse. Qualitative methods are used with data collection through active participation, interviews, and literature studies, as well as analysis based on normative, ideal, and factual roles according to Soerjono Soekanto. BNN RI Public Relations actively uses social media according to norms and policies, strives to meet public expectations, and has produced various prevention content. TikTok has proven to be the most effective platform with video statement content that attracts users' attention. However, challenges such as negative feedback and limited resources still need to be overcome. It is recommended that BNN RI Public Relations continue to develop digital communication strategies, expand reach, improve content quality, and strengthen collaboration to optimize drug prevention in Indonesia.